2009
DOI: 10.1021/cg9001048
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Clathrate Hydrates Formed at the Interface of Liquid Water and Gaseous Methane, Ethane, or Propane: Variations in Crystal Morphology

Abstract: This paper reports the visual observations of the formation and growth of clathrate hydrate crystals on the surface of a water droplet exposed to gaseous methane, ethane, or propane. The hydrate crystals formed and grew at the guest-water interface. The nucleation of the hydrate first occurred at a random point on the water droplet and then grew to form a polycrystalline layer covering the surface. We observed the individual crystals that constitute the polycrystalline hydrate layer and classified the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
153
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(174 citation statements)
references
References 11 publications
16
153
2
1
Order By: Relevance
“…47 Inhibition performance can be monitored and compared through use of high pressure apparatus in which gas consumption indicates hydrate formation (an increased gas consumption is indicative of hydrate formation and therefore an ineffective inhibitor). 47 Inhibitors 2 85 and 3 are found to have significantly reduced gas consumption relative to 1 (when analysed at 277.2 K). 47 As a continuation of their work in this field, CSM investigated the inhibition properties of 3 which at the time was being 90 synthesised for alternative application within the hair-care industry.…”
Section: Development Of Khismentioning
confidence: 95%
See 4 more Smart Citations
“…47 Inhibition performance can be monitored and compared through use of high pressure apparatus in which gas consumption indicates hydrate formation (an increased gas consumption is indicative of hydrate formation and therefore an ineffective inhibitor). 47 Inhibitors 2 85 and 3 are found to have significantly reduced gas consumption relative to 1 (when analysed at 277.2 K). 47 As a continuation of their work in this field, CSM investigated the inhibition properties of 3 which at the time was being 90 synthesised for alternative application within the hair-care industry.…”
Section: Development Of Khismentioning
confidence: 95%
“…28 The synthesis of glycoproteins has been undertaken and proven to be successful at interfering with hydrate crystal growth, however it did not prove to be an economically viable inhibition methodology. 34 Several studies 85 have been reported which compare the efficacy of AFPs with synthetic KHIs such as poly(N-vinyl pyrrolidone) (PVP, 1), indicating that AFPs may hold advantages in prolonging induction periods by having a more pronounced effect upon nucleation. 35 There has been considerable work probing the mechanism of action of AFPs at inhibiting ice growth, reporting a surface adsorption mechanism and the resulting Kelvin effect.…”
Section: Development Of Khismentioning
confidence: 99%
See 3 more Smart Citations